111k views
18 votes
Hi. I need help with this question (see image). Please show workings.​

Hi. I need help with this question (see image). Please show workings.​-example-1

1 Answer

10 votes

Answer:


(dy)/(dx) = 2x - 3 -
(10)/(x^3)

Explanation:

Given

y =
(x^4-3x^3-4x^2+5)/(x^2)

Divide each term on the numerator by x²

y = x² - 3x - 4 + 5
x^(-2)

Differentiate each term using the power rule


(d)/(dx) (a
x^(n) ) = na
x^(n-1)


(dy)/(dx) = 2x - 3 - 0 - 10
x^(-3)

= 2x - 3 -
(10)/(x^3)

User Slifty
by
5.1k points